2013
DOI: 10.1590/s0104-07072013000400007
|View full text |Cite
|
Sign up to set email alerts
|

A tecnologia de grupo operativo aplicada num programa de controle do tabagismo

Abstract: This descriptive and exploratory study was performed with the purpose to discuss the use of group operative technology as a coping strategy in a tobacco control program in the primary health care system of a small municipality in the state of Goiás, Brazil. The subjects were 20 individuals who sought the Primary Health Care Unit on their own account, and the sample consisted of nine people who completed the treatment. Content analysis revealed the thematic category: The path followed during the treatment; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
3
0
4
Order By: Relevance
“…No que tange a esse achado, a literatura traz que as informações quanto aos malefícios do consumo de cigarro para a saúde são difundidas mundialmente, mas só esse fato parece insuficiente para levar as pessoas a pararem de fumar. No entanto, percebe-se que o conhecimento sobre os agravos à saúde que o tabaco acarreta e a presença desses males auxilia o fumante a observar e a relacionar suas disfunções corporais/mentais ao seu vício (Lucchese, et al, 2013).…”
Section: Discussionunclassified
“…No que tange a esse achado, a literatura traz que as informações quanto aos malefícios do consumo de cigarro para a saúde são difundidas mundialmente, mas só esse fato parece insuficiente para levar as pessoas a pararem de fumar. No entanto, percebe-se que o conhecimento sobre os agravos à saúde que o tabaco acarreta e a presença desses males auxilia o fumante a observar e a relacionar suas disfunções corporais/mentais ao seu vício (Lucchese, et al, 2013).…”
Section: Discussionunclassified
“…A study carried out in the Primary Health Care of a city in the center-west of Brazil, in which the operative group was used as a strategy to cope with the cessation of tobacco use, showed that the dropout rate reached 78% (35) . Despite the possibility that a significant portion of individuals participating in an anti-smoking group may resume smoking over time, as identified in a study conducted in Maringá-PR, Brazil (36) , it is clear that this behavior should be continually encouraged by health professionals and, where possible, involve the family in this task, as cessation of smoking is a complex process.…”
Section: Discussionmentioning
confidence: 99%
“…15 The survey of the social determinants and the interrelationships of smoking men may also culminate in the readjustment of the implemented actions, especially those that use groups, according to a study carried out in Goiás, which found a smoking dropout rate of 78% , after the application of Operating Groups. 16 However, public policies aimed at combating smoking have reproduced traditional actions of a strictly scientific and prescriptive nature, however, a North American study carried out at national level with 6,203 adults, pointed out that the level of religiosity was inversely associated with the use of licit and illicit psychoactive substances, which includes tobacco derivatives. 17 The association found in this current study between religion and the lower proportion of smoking may be related to the belief in dogmas and the possible consequences of errors and sins, among them, addictions such as smoking.…”
Section: Discussionmentioning
confidence: 99%